KARAKTERISTIK HIDROFOBISITAS PERMUKAAN PERANCAH DILIHAT DARI CONTACT ANGLE SERTA PENYUSUNAN ALAT UNTUK REGENERASI JARINGAN TULANG - Meibi Murbi Arlianata (FKG 16 UMY, 2016)
Fractures or fractures can be caused by physical exertion and accident trauma . Accident ( Intra cranial injury ) already ranks as the second largest cause of death and injury . Tissue engineering or tissue engineering is a technique that can create complex network from simple networks.Three major component in thatfield is : Scaffold cell and growth factors . Characters that must be owned by a bone replacement material (bone graft ) is a character hydrophobicity . Objective : To see how big the hydrophobicity formed on the surface of the scaffold were very small , measurements were taken using a Rame Hart goniometer . The simple principle of this tool can be replaced with a DSLR camera preparation and tripod. Method : This study was an experimental laboratory. Samples are artificial coral scaffold various concentrations , which consists of 3 different concentration concentration of gelatin : CaCO3 4 : 6 , 7 : 3 , and gelatin 100 % , which would be distilled water droplets and will be in the photo. Analysis of data using oneway ANOVA and Kruskal Wallis . Result : Levene 's Test ( Table 4 ) shows the significant value of 0.397 ( p > 0.05 ) , the variance of the data is same, so we proceed to Oneway ANOVA test . Oneway ANOVA test obtained probability value was 0.109 > 0.05 then H0 is accepted, meaning that there is no significant difference . Conclusion : No difference Contact Angle drops of distilled water on coral scaffold and gelatin ratio of 4 : 6 , 7 : 3 and 100 % gelatin significantly . The contact angle value is on the scaffold with a concentration of 4 : 6 , then 100 % and the last one is 7 : 3 . Keywords : hydrophobic , bone regeneration , coral scaffold cell